Virtual Prediction of The Potency of Common Jasmine (Jasminum officinale L.) Bioactive Compounds as Anti-Aging Agents for Natural Sunscreen - Fathiyah Nurul Izzah; Dawama Nur Fadlilah; Yohanna Sisilia Grace Sirait; Nandagesta Aurelia Shafa Wagmi; Abdullah Abdullah; Turhadi Turhadi; Fatchiyah Fatchiyah (JSMARTech: Journal of Smart Bioprospecting and Technology, 2022)
UV exposure causes protein denaturation in the skin, leading to wrinkles and photoaging. Matrix metalloproteinases (MMPs) are enzymes that degrade the matrix and are associated with destruction processes like skin aging. Tyrosinase is the rate-limiting enzyme in the melanin synthesis process. We predict that Jasminum officinale L. bioactive compounds can be used as inhibitors for MMP1, MMP3, and tyrosinase. This study aims to compare the potential of bioactive compounds in Jasminum officinale L. as an inhibitor for the MMP1, MMP3, and tyrosinase receptors to prevent anti-aging. Vanillin, hydroxytyrosol, salicylic acid, 3,4-dihydroxy benzoic acid, oleoside-11-methyl ester, ursolic acid, oleanolic acid, and jasminine were retrieved from PubChem database as ligands, to dock with MMP1, MMP3, and tyrosinase as receptors that were retrieved from RCSB PDB. ADMET analysis was performed using pKCSM. Target-based virtual screening was performed using AutoDock Vina in PyRx. Visualization and interactions of amino acid residues was performed using Biovia Discovery Studio 2021. The complex structure was analyzed by molecular dynamics using the CABS-Flex 2.0 website. The oleoside-11-methyl ester compound has the highest potential as an MMP1 inhibitor, the 3,4-dihydroxy benzoic acid compound has the potential to inhibit MMP3, and hydroxytyrosol has the potential to inhibit tyrosinase involved in skin aging because it has low toxicity, highest binding affinity, and low fluctuations based on RMSF values in molecular dynamics simulations. Thus, this study indicated that bioactive compounds in common jasmine (Jasminum officinale L.) can be used as a candidate for organic sunscreen.